TEKNIK IMOTILISASI IKAN KERAPU CANTANG (Epinephelus sp.) MENGGUNAKAN EKSTRAK DAUN KECUBUNG (Datura metel L.) - Akbar, Rusdi; Jumsurizal, Jumsurizal; Putri, R. Marwita Sari (Marinade, 2021)
The immotilization technique of cantang grouper (Epinephelus sp.) Using Datura metel L. leaf extract. The purpose of this study was to find the best concentration at onset time of Datura metel L. leaves as anesthetic agent for grouper (Epinephelus sp.) And its survival rate. The results of the study, using extracts of natural anesthetic ingredients of amethyst leaves with concentrations of 20%, 25%, and 30% had different effects (P